The essay film : from Montaigne, after Marker - Corrigan, Timothy, 1951- (Oxford University Press, 2011)
"Why have certain kinds of documentary and non-narrative films emerged as the most interesting, exciting, and provocative movies made in the last twenty years? Ranging from the films of Ross McElwee (Bright Leaves) and Agnes Varda (The Gleaners and I) to those of Abbas Kiarostami (Close Up) and Ari Folman (Waltz with Bashir), such films have intrigued viewers who at the same time have struggled to categorize them. Sometimes described as personal documentaries or diary films, these eclectic works are, rather, best understood as cinematic variations on the essay. So argues Tim Corrigan in this stimulating and necessary new book. Since Michel de Montaigne, essays have been seen as a lively literary category, and yet--despite the work of pioneers like Chris Marker--seldom discussed as a cinematic tradition. The Essay Film, offering a thoughtful account of the long rapport between literature and film as well as novel interpretations and theoretical models, provides the ideas that will change this." --